2016
DOI: 10.17221/207/2015-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

A study on research hot-spots and frontiers of agricultural science and technology innovation - visualization analysis based on the Citespace III

Abstract: At present, the fundamental development way of agricultural production lies in science and technology to achieve the agricultural sustainable and stable development and ensure the eff ective supply of agricultural products for a long time. Many Chinese scholars had done many researches about the agricultural science and technology innovation. Numerous scholars got much valuable research conclusions for improving the construction of agricultural science and technology innovation system. However, there were stil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Not only the bibliometric analysis but also the visualization of literature is used widely to analyze the relevant research data in many research fields, such as psychometric, nanotechnology, aviation engineering, economic geography, ecological security and science, strategic management, and technology policy analysis. 14 However, the bibliometric analysis about nurses, especially the NPs, still produced only sparse results. In order to explore more about the development tendency and hotspots in this field, the CiteSpaceV software has been used in the visualization related to NPs.…”
Section: Methods Of Analysismentioning
confidence: 99%
“…Not only the bibliometric analysis but also the visualization of literature is used widely to analyze the relevant research data in many research fields, such as psychometric, nanotechnology, aviation engineering, economic geography, ecological security and science, strategic management, and technology policy analysis. 14 However, the bibliometric analysis about nurses, especially the NPs, still produced only sparse results. In order to explore more about the development tendency and hotspots in this field, the CiteSpaceV software has been used in the visualization related to NPs.…”
Section: Methods Of Analysismentioning
confidence: 99%
“…Wang et al (2020) found that technological innovation could drive the transformation of the economic development mode, and economic development provided financial support for technological innovation, which showed coordination [ 9 ]. Some scholars have proposed to use technological innovation to promote the development of agricultural economy, and have pointed out that it was necessary to promote the role of technological innovation in the transformation of agricultural economic development from various aspects such as policy, investment, organizational construction, and the creation of an entrepreneurial environment [ 10 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The research topics or special issues of papers are displayed through keywords, which are the core of academic papers (Qi-Qi et al, 2016). Therefore, keyword analysis can draw the research objects, contents, and hotspots of a certain research field.…”
Section: Abstract Analysismentioning
confidence: 99%
“…When literature A and literature B are cited simultaneously by literature C and other literature, A and B are called co-cited. By analyzing the cited literature and co-cited literature, we can provide intuitive tools for exploring the knowledge domain and frontiers of scientific research fields (Chen et al, 2010;Qi-Qi et al, 2016).…”
Section: References Analysismentioning
confidence: 99%